Anogeissus leiocarpus (DC.) Guill. & Perr. extract-protected rats against CCl4-induced liver fibrosis - Omokolade O. Alejolowo, MSc; Olarewaju M. Oluba, PhD; Oluyomi S. Adeyemi, PhD (Journal of Taibah University Medical Sciences, 2025)
الملخص: أهداف البحث: يستخدم مستخلص لحاء ساق أنوجيسوس ليوكاربوس (جيل وبير) موضعيا لعلاج اختلال وظائف الكبد في نيجيريا. بحثت هذه الدراسة في التأثير الوقائي للكبد لمستخلص لحاء ساق أنوجيسوس ليوكاربوس الهيدروميثانولي في تليف الكبد الناتج عن رباعي كلوريد الكربون لدى فئران ويستار. طرق البحث: قسم خمسة وثلاثون فأرا ذكرا عشوائيا إلى سبع مجموعات. تلقت المجموعة الأولى (مجموعة الضبط) الماء المقطر وزيت الزيتون، بينما تلقت المجموعة الثانية (مجموعة الضبط السلبية) ٣۰٪ من رباعي كلوريد الكربون عن طريق الحقن البريتوني في زيت الزيتون ثلاث مرات أسبوعيا لمدة ثمانية أسابيع. بالإضافة إلى رباعي كلوريد الكربون، أُعطيت فئران المجموعات من الثالثة إلى السادسة سيليمارين عن طريق الفم (مجموعة الضبط الإيجابية) وجرعات متدرجة (١۲٥، ۲٥۰، و ٥۰۰ ملغم/كغم من وزن الجسم) من مستخلص لحاء ساق أنوجيسوس ليوكاربوس الهيدروميثانولي، على التوالي. تلقت المجموعة السابعة (مجموعة المتابعة) رباعي كلوريد الكربون فقط، ولكن تم إبقاؤها لمدة أسبوعين آخرين قبل التشريح. بعد ثمانية أسابيع، تم تشريح الحيوانات، وأجريت لها تقييمات بيوكيميائية ونسيجية ومناعية نسيجية متنوعة. النتائج: كشف تحليل جهاز استشراب سائل عالي الأداء لـ أنوجيسوس ليوكاربوس عن ثلاثة عشر مركبا، بما في ذلك حمض الغال والكاستالاجين. أدى التعرض لـ ''سي سي إل ٤'' إلى زيادة ملحوظة في مؤشر الكبد مقارنةً بالمجموعة الضابطة، إلا أن ارتفاع مؤشر الكبد تحسن بعد إعطاء أنوجيسوس ليوكاربوس. رفع أنوجيسوس ليوكاربوس معايير مضادات الأكسدة، بما في ذلك مستويات ''اس او دي'' و ''جي بي اكس'' و ''جي اس اتش''، مع انخفاض مماثل في مستويات المالونديالدهيد. علاوة على ذلك، تسبب أنوجيسوس ليوكاربوس في انخفاض مستوى ''تي ان اف-ألفا'' و ''انترليوكن-٦'' في البلازما مقارنة بمجموعة ''سي سي إل ٤''. أدى العلاج بـ أنوجيسوس ليوكاربوس إلى تخفيف انتفاخ الخلايا الكبدية بشكل معتدل، مع تقليل التعبير عن ''ألفا-اس ام ايه'' الكبدي و''تي جي اف-بيتا'' مقارنة بـ ''سي سي إل ٤''. تشير النتائج إلى أن التأثير المضاد للتليف لـ أنوجيسوس ليوكاربوس قد يتضمن تثبيط التعبير عن ''ألفا-اس ام ايه'' و ''تي جي اف-بيتا''. علاوة على ذلك، حسن أنوجيسوس ليوكاربوس بشكل ملحوظ مؤشرات وظائف الكبد (ألانين ترانساميناز، وأسبارتات ترانساميناز، والفوسفاتاز القلوي) بشكل مماثل لتلك الموجودة في المجموعة الضابطة ومجموعة العلاج بـ ''سي سي إل ٤'' مع سيليمارين. الاستنتاجات: أظهر مستخلص لحاء ساق أنوجيسوس ليوكاربوس بشكل عام تأثيرا مضادا للالتهابات، وواقيا للكبد، ومضادا للتليف؛ وبالتالي، لديه آفاق لمزيد من الاستكشاف كعلاج محتمل لأمراض الكبد. Abstract: Objective: Anogeissus leiocarpus (DC.) Guill. & Perr. is locally used for the treatment of hepatic dysfunctions in Nigeria. This study investigated the hepatoprotective impact of A. leiocarpus stem bark hydromethanolic extract (AL) in carbon tetrachloride (CCl4)-induced hepatic fibrosis in Wistar rats. Methods: Thirty-five male rats were randomly assigned to seven groups. Group I (control) received distilled water and olive oil, and Group II (negative control) received 30 % CCl4 intraperitoneally in olive oil three times a week for 8 weeks. In addition to CCl4, rats in groups III–VI were orally given silymarin (positive control) and graded doses (125, 250, and 500 mg/kg body weight) of AL. Group VII (follow-up group) received CCl4 only, but was spared for another 2 weeks before necropsy. After 8 weeks, the animals were necropsied, and various biochemical, histological, and immunohistochemical assessments were conducted. Results: High-performance liquid chromatography analysis of AL detected 13 compounds, including gallic acid and castalagin. CCl4 exposure led to a significant increase in liver index relative to the control, but the increased liver index improved following AL administration. AL elevated the antioxidant parameters, including the levels of superoxide dismutase, glutathione peroxidase, and glutathione peroxidase, with a corresponding decline in malondialdehyde levels. Furthermore, AL caused a decline in the plasma level of tumor necrosis factor alpha and interleukin 6 relative to the CCl4 group. AL treatment moderately thinned the hepatocyte ballooning, while reducing the expression of hepatic alpha smooth muscle actin (α-SMA) and transforming growth factor beta (TGF-β) compared with CCl4. These findings indicate that the antifibrotic action of AL might involve the downregulation of α-SMA and TGF-β expression. Furthermore, AL appreciably improved liver function indices (alanine transaminase, aspartate transaminase, and alkaline phosphatase) in a manner comparable to that of the control and CCl4 + silymarin treatment groups. Conclusion: Collectively, AL exhibited anti-inflammatory, hepatoprotective, and antifibrotic effects and thus has prospects for further exploration as a potential therapy in liver diseases.